Intravitreal Plungerless Injector Device (IPLID): An Innovative Intravitreal Injector Device - Yepez JB; Murati FA; Petitto M; Kozak I; Arevalo JF (Clinical Ophthalmology)
Juan B Yepez,1 Felipe A Murati,2 Michele Petitto,3 Igor Kozak,4 J Fernando Arevalo5 1Vitreoretinal Surgery Department, Clinica de Ojos, Maracaibo, Venezuela; 2Sotero del Rio, Hospital, Santiago, Chile; 3Glaucoma Department, Clinica de Ojos, Maracaibo, Venezuela; 4Department of Ophthalmology and Vision Science, University of Arizona, Tucson, AZ, USA; 5Retina Division, Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USACorrespondence: J Fernando Arevalo, Retina Division The Wilmer Eye Institute, Johns Hopkins University School of Medicine, 600 N. Wolfe Street, Maumenee 713, Baltimore, MD, 21287, USA, Tel +1 443 287 9554, Fax +1 443 287 5492, Email arevalojf@jhmi.eduPurpose: To share our early experience with the novel intravitreal plungerless injector device (IPLID) for application in patients with various retinal diseases.Patients and Methods: This study enrolled 300 eyes (300 patients) who had undergone at least 1 previous conventional intravitreal injection, for various indications, such as diabetic macular edema, venous occlusions, active choroidal neovascular membrane, wet AMD and neovascular glaucoma. Patients with systemic conditions that could affect pain tolerance were excluded. All patients underwent intravitreal injection with the IPLID. After the procedure the patients were asked to grade pain compared to conventional injections. Immediately after the procedure, surgeons completed a simple survey on various aspects of the device, including safety of the procedure. Data were also collected on the duration of the procedure.Results: The study sample was comprised of 210 males and 90 females. The mean duration of the injection was 17.51 minutes (range, 15 minutes to 20 minutes). Post-IPLID injection, 155 (51.7%) patients reported less pain compared to previous injections, 128 (42.7) patients reported pain similar to previous injections and 5.7% (17) of patients reported more pain than previous procedures. The physician survey indicated that there was no difference between IPLID and conventional technique in 13.33% (40) of injections, and 86.67% (260) of the injections were comfortable to perform with the IPLID and size was not an issue in 91.67% (275) of injections. In all cases, the surgeons were comfortable with the delivery of medication with IPLID and there were no adverse events during or after IPLID injection.Conclusion: The IPLID is a simple device for delivering intravitreal injection and may offer greater ergonomic advantages and that address the issue of musculoskeletal disorders in healthcare personnel due to repetitive procedures over time.Keywords: intravitreal injections, IPLID, hand ergonomics, musculoskeletal disorders